Empirical Research Regarding the Migration of Highly Qualified Human Resources From Romania - Example from the Medical Field - Popescu, Dan; Picu, Cătălina Georgiana; Popescu, Andrei-Constantin (European Journal of Sustainable Development, 2018)
As a direct consequence of globalisation and internationalization on the one hand and of the liberalization of markets and technological advances on the other hand, the international migration of highly qualified human resources is experiencing an ever more alarming growth because of its size and, in particular, of its implications. Adapting to a more and more unpredictable socio-economic environment, as a result of a fierce struggle for survival and for sustainable development requires that each and every company globalises its strategies, structures, resources and markets. The progress achieved in terms of technique and technology, along with the liberalization of the commodities, services and capital markets have generated new opportunities, as well as new threats for the organizations all over the world. Our research aims at highlighting to what extent the international migration of highly qualified human resources from Romania - in particular in the healthcare sector – can have a severe impact on the prospects of Romania’s sustainable and durable economic development. At the end, we formulate a number of proposals, which, in our opinion, could decrease the exodus of highly qualified human resources, and especially that of medical doctors, to third markets. Keywords: qualified human resources, brain drain, migration, medical doctors